Grammatical Prohibitions In The Transitivity Of Verbs According To Al-Rummani: A Study Of What Is Not Permissible In His Commentary On Sibawayh’s Book/ المحظورات النَّحويَّة في تعدِّي الأفعال عند الرُّمَّانيّ: دراسة في ما لا يجوز في شرحه لكتاب سيبويه - Halima Talib Jumaa; Wissam Najm Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study seeks to examine and analyze Al-Rummani’s grammatical positions in